Podoba epidemije v starejših poljudnostrokovnih in publicističnih besedilih - Ulčnik, Natalija (Slavia Centralis, 2020)
THE IMAGE OF THE EPIDEMIC IN OLDER POPULAR PROFESSIONAL AND JOURNALISTIC TEXTS The article is based on select popular science books and newspaper articles and focuses on the reporting of the cholera epidemic in the 19th century and early 20th century. The analyses are performed on the level of the key contextual elements and on the linguistic-stylistic level. It draws attention to the parallels between older and contemporary texts which describe the epidemic. The analyses focus on expressiveness and the use of rhetorical devices, e.g. personifications (the disease visits us, it comes, does not mean to say goodbye…) and metaphors (illness as a stranger, murderer, monster). At the lexical level, the analysis points out the terms which in the time of epidemic often occur as early as in 19th century, e.g. epidemic, hygiene, quarantine, isolate, disinfect. These lexemes effectively indicate crucial themes in the analysed texts and at the same time reflect the social reality of the time.